2009
DOI: 10.1007/s12011-009-8328-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium on Wheat Seedlings Under Drought Stress

Abstract: The paper reports the effects of selenium (Se) supply on growth and some physiological traits of wheat (Triticum aestivum L. cv Shijiazhuang NO. 8) seedlings exposed to drought stress. The growth and physiological responses of seedlings were different depending on the Se concentration. The higher (3.0 mg Se kg(-1)) and lower amount used (0.5 mg Se kg(-1)) did not significantly affect on biomass accumulation. Treatments with 1.0 and 2.0 mg Se kg(-1) promoted biomass accumulation of wheat seedlings. Treatments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
86
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(102 citation statements)
references
References 21 publications
(23 reference statements)
14
86
0
2
Order By: Relevance
“…Our result demonstrated that the role of Se could enhance the POD activity. This is in agreement with the findings of Yao et al [12], who found that Se supply significantly increased POD activity under drought stress.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our result demonstrated that the role of Se could enhance the POD activity. This is in agreement with the findings of Yao et al [12], who found that Se supply significantly increased POD activity under drought stress.…”
Section: Discussionsupporting
confidence: 94%
“…Lipid peroxidation was estimated by measuring the content of malondialdehyde (MDA) using the thiobarbituric acid (TBA) assays as described by Yao et al [12]. Leaves tissues (0.5 g) were extracted in a solution of 20% (w/v) trichloroacetic acid containing 0.5% (w/v) TBA and 4% (w/v) butylated hydroxytoluene.…”
Section: Lipid Peroxidationmentioning
confidence: 99%
“…Drought stress reduced growth activity of barley (Tables 1), as is observed by other plants species (Ramesh, 1999;Liu and Stützel, 2004;Degu et al, 2008). Recently, Yao et al (2009) suggested that optimal Se supply is favorable for growth of wheat seedlings during drought condition. In this work, however, selenium spraying could not improve growth parameters under drought conditions.…”
Section: Discussionsupporting
confidence: 60%
“…A significantly higher actual photochemical efficiency of PSII was obtained in Sesupplemented water-deficit plants, which was possibly due to improvement of plant water management during treatment (Tadina et al, 2007). Selenium supply is favorable for growth of wheat seedlings during drought condition, however, the growth and physiological responses of seedlings were different, depending on the Se concentration (Yao et al, 2009). Simojoki (2003) reported that small Se addition that increased Se contents in lettuce shoots tend to enhance plant growth.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation